Modified vaccinia virus Ankara triggers type I IFN production in murine conventional dendritic cells via a cGAS/STING-mediated cytosolic DNA-sensing pathway. - Peihong Dai; Weiyi Wang; Hua Cao; Francesca Avogadri; Lianpan Dai; Ingo Drexler; Johanna A Joyce; Xiao-Dong Li; Zhijian Chen; Taha Merghoub; Stewart Shuman; Liang Deng (PLoS Pathogens)
Modified vaccinia virus Ankara (MVA) is an attenuated poxvirus that has been engineered as a vaccine against infectious agents and cancers. Our goal is to understand how MVA modulates innate immunity in dendritic cells (DCs), which can provide insights to vaccine design. In this study, using murine bone marrow-derived dendritic cells, we assessed type I interferon (IFN) gene induction and protein secretion in response to MVA infection. We report that MVA infection elicits the production of type I IFN in murine conventional dendritic cells (cDCs), but not in plasmacytoid dendritic cells (pDCs). Transcription factors IRF3 (IFN regulatory factor 3) and IRF7, and the positive feedback loop mediated by IFNAR1 (IFN alpha/beta receptor 1), are required for the induction. MVA induction of type I IFN is fully dependent on STING (stimulator of IFN genes) and the newly discovered cytosolic DNA sensor cGAS (cyclic guanosine monophosphate-adenosine monophosphate synthase). MVA infection of cDCs triggers phosphorylation of TBK1 (Tank-binding kinase 1) and IRF3, which is abolished in the absence of cGAS and STING. Furthermore, intravenous delivery of MVA induces type I IFN in wild-type mice, but not in mice lacking STING or IRF3. Treatment of cDCs with inhibitors of endosomal and lysosomal acidification or the lysosomal enzyme Cathepsin B attenuated MVA-induced type I IFN production, indicating that lysosomal enzymatic processing of virions is important for MVA sensing. Taken together, our results demonstrate a critical role of the cGAS/STING-mediated cytosolic DNA-sensing pathway for type I IFN induction in cDCs by MVA. We present evidence that vaccinia virulence factors E3 and N1 inhibit the activation of IRF3 and the induction of IFNB gene in MVA-infected cDCs.